The Effects of Learning Mandarin Online with a Native Lecturer to University Students’ Anxiety - Juairiah Nastiti Sandyaningrum; Dani Putri Septi Kusumaningtyas (Mandarinable: Journal of Chinese Studies, 2023)
The Diploma Mandarin Language Study Program at UNS transitioned to online learning as an alternative to face-to-face instruction following the COVID-19 pandemic. Foreign language learning, including Mandarin Chinese, typically involves native speakers as instructors. However, online learning with native speakers can inadvertently result in student anxiety. To address this issue, the program collaborated with the UNS Confucius Institute to bring native lecturers onboard. Nevertheless, certain native lecturers encountered visa-related challenges that prevented them from teaching in a face-to-face setting. Inspired by the post-COVID online learning landscape, the Study Program formulated a policy to continue certain Chinese language courses online.This study aims to analyze the impact of online Chinese language learning with native lecturers on the levels of anxiety among Diploma Mandarin Language students. A quantitative approach was employed, utilizing a case study design and data collection techniques, including observation and questionnaires. The research seeks to contribute theoretically by addressing the gaps in the literature related to student anxiety during online Mandarin learning with native speakers. The study involved 30 randomly selected students from the Diploma Mandarin Language classes of 2021 and 2022 at UNS. The results of this study indicated that 73.33% of the respondents experienced anxiety while participating in online learning with native instructors. The types of anxiety included reduced learning conditions, diminished self-efficacy, and decreased learning effectiveness.